Twist metrology with twisted light in fibers - Yijie Shen (Light: Advanced Manufacturing)
A recent breakthrough of optical metrology is the all-fiber rotational Doppler velocimetry using twisted light, which offers a compact, reciprocal, and ultra-broadband solution for measuring the angular velocity of rotating objects.